Partisipasi Penganggaran & Keadilan Prosedural Untuk Meningkatkan Kinerja (Studi Di Pt. Karana Line Surabaya) - Wahyuningsari, Hanita; Hastuti, Sri (Jurnal Riset Ekonomi dan Bisnis, 2010)
These days, growth of corporate world in Indonesia progressively rapidly grow and intercompany emulation become progressively tighten. At the time of taking decision, good manager is manager having organizational ability and exploit the resource which is available in effort to reach the company target. All manager need the appliance which can assist the planning, coordination and performance assessment, that is budget. This Research target is to test empirically is influence from participation of budgeting and justice prosedural to managerial performancePopulation is 16 related personal with the budget compilation that is from top until lower management PT. Karana of Line Surabaya. Technique sampel used by census method, where all population member made by as sampel, consisted of by 1 head branch, 4 superintendent, and 11 sub units head. This Research data use the primary data with the instrument kuesioner. Technics analyse used by a Multiple Linear Regression.Pursuant to examination result obtained by conclusion that budgeting participation have an effect  on to manajerial performance, justice prosedural have an effect on to manajerial performance.Keyword :  Budgeting Partisipation, Procedural Justice, Manajerial Performance